2006
DOI: 10.1007/s10740-006-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

A new equation of state for rubidium vapors at temperatures up to 1600 K and pressures up to 4 MPa

Abstract: Statistical matching is performed of a wide range of diverse experimental data on the thermodynamic properties of saturated and superheated rubidium vapors at temperatures up to 1650 K. The parametric models used in the matching of data include the equation of state in the virial form and equations in the form of group expansions in terms of degrees of activity. Values of the second virial and group coefficients are obtained using new spectroscopic data on the singlet potential of rubidium atoms in the ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Comparison of the obtained values of with the results of similar calculation by Mozgovoi et al [21] revealed the difference of 0.15% at 1000 K, 0.5% at 1500 K, and 1% at 2000 K. The resultant divergences are within the overall error of both calculations. Possibly, they are explained in part by the fact that Sinanoglu and Pitzer [20] approximated the triplet interaction potential by the model Morse potential.…”
Section: Calculation Resultssupporting
confidence: 75%
“…Comparison of the obtained values of with the results of similar calculation by Mozgovoi et al [21] revealed the difference of 0.15% at 1000 K, 0.5% at 1500 K, and 1% at 2000 K. The resultant divergences are within the overall error of both calculations. Possibly, they are explained in part by the fact that Sinanoglu and Pitzer [20] approximated the triplet interaction potential by the model Morse potential.…”
Section: Calculation Resultssupporting
confidence: 75%
“…The experimental data of this study were used in deriving the equation of state (ES) for rubidium vapors by simultaneously treating different thermodynamic properties in wide ranges of parameters of state [11]. The difference between these data and the values of the velocity of propagation of ultrasound in saturated rubidium vapors, calculated by the ES of rubidium vapors ( ρ ES ), are given in Fig.…”
Section: Experimental Investigation Of the Velocity Of Sound In Saturmentioning
confidence: 99%
“…This difference is within the confidence error of the experiments and is estimated by us at 0.5% or less. (1) and (2) and by the equation of state for rubidium vapors [11].…”
Section: Experimental Investigation Of the Velocity Of Sound In Saturmentioning
confidence: 99%
“…Common virial EoS's for alkali vapors found by fitting Eq. ( 1) to the experimental data and given in the handbook [27] include from four to seven contributions in virial expansion (1) and may contain twenty or more parameters [28,29,30]. In such a situation, the following question arises quite naturally: Is it possible to formulate a simple effective analytical model that could reproduce the experimental data for thermal EoS of alkali elements in a gas phase?…”
Section: Introductionmentioning
confidence: 99%